3D Nano‐structure L‐cysteine/AuNPs/Bi2O3 Modified Glass Carbon Electrode as Chemical Sensor for Highly Sensitive and Selective Detection Cu (II). Issue 9 (9th May 2016) - Zhou, Enhong; Wu, Ju; Li, Linna; Yang, Mei; Jin, Juncheng; Fu, Xucheng; Chang, Wengui; Xie, Chenggen
Abstract: It was first time using the l‐cysteine self‐assembled on the surface of gold nanoparticles and Bi2 O3 nano‐structured materials modified GCE composed l‐cysteine/AuNPs/Bi2 O3 /GCE sensor. The sensor possessed three‐dimensional nanostructure and exhibited a higher ratio of activity sites, large active surface, fast electron transfer rate, excellent catalytic, sensing characteristics and larger affinity to Cu (II). The sensor was determined to have an excellent sensitivity and selectivity for the detection of Cu (II). The characterization of sensor as well as the optimization of the analytical procedure was reported. The optimized conditions parameters allowed the detection of Cu (II) concentration following short analysis time, a detection limit of 5×10 −11  M at 80 s of preconcentration time was obtained using the as‐prepared sensor, and also show excellent stability and good repeatability, and, thus, could be used for detection of Cu (II) in environment. Abstract :